Effect of Overlapping Remelting on Microstructures and Mechanical Properties of Selective Laser‐Melted Ti‐6Al‐4V Alloy. Issue 3 (10th December 2021) - Wang, Qipeng; Kong, Jian; Liu, Xiangkui; Song, Xinxiang; Dong, Kewei; Yang, Yang
Abstract : Selective laser melting (SLM) is a common technology of additive manufacturing in which the factors determining the final performance are laser power, scanning speed, powder thickness, energy density, to name a few. Herein, the mechanical properties and microstructures of Ti‐6Al‐4 V alloy prints, prepared by SLM technology under different overlapping remelting areas and energy densities, are systematically investigated. The results indicate that with the overlapping remelting area and energy densities increasing, the maximum pore diameter and the number of relatively large pore decrease, and the thickness of the prior‐β lamellae and the number of the nano‐β phase precipitated increase, which plays a significant role in the mechanical properties. Concretely, the mechanical performances of the as‐built Ti‐6Al‐4 V alloys are enhanced due to the decrease of large pores. Moreover, the β phase precipitated and the thick β lamellae can dramatically improve the strength and plasticity, respectively. When the overlapping ratio and volume energy density reach up to 20% and 44.05 J mm −3, respectively, the comprehensive mechanical properties under the synergistic effect of pores and microstructures stand out. Abstract : The decrease of the maximum pore diameter and the number of large pore, along with the increase of the number of β phase precipitated can significantly enhance the strength. The increase of the lamellae thickness simultaneously improves the plasticity and reduces the strength. Therefore, when the overlapping ratio approaches 20%, the comprehensive mechanical properties are better.